Principles of general chemistry - Silberberg, Martin S. (McGraw-Hill Higher Education, 2007)
Silberberg’s Principles of General Chemistry offers students the same authoritative topic coverage as his 4th edition textbook while appealing to today’s efficiency-minded and value-conscious instructors and students. Principles allows for succinct coverage of content with minimal emphasis on pedagogic learning aids. This new approach offers a more straightforward approach to learning the core principles without sacrificing depth, clarity, or rigor